PENGARUH PENAMBAHAN TEPUNG KEDELAI (Glycine max L.) PADA PEMBUATAN BISKUIT BEBAS GLUTEN BEBAS KASEIN BERBAHAN BAKU TEPUNG PISANG GOROHO (Musa acuminate L.). - Efraim B. Thomas; Erny J.N. Nurali; Thelma D.J. Tuju (COCOS, 2017)
ABSTRACTThe aim of this research was to find the exact amount of soybean flour addition which is precisely based on physicochemical qualities and sensory properties of casein-free gluten free (CFGF) biscuits made from raw goroho plantain flour. This study used Completely Randomized Design (RAL) with five treatments ie A (without soybean addition), B (10% soybean flour), C (15% soybean flour), D (20% soybean flour), E (25%) Each treatment was repeated three times. Parameters analyzed included sensory tests of taste, color, aroma, crispness, moisture content, ash content, protein content, fat content, carbohydrate, calorific value and hardness of biscuit. The results showed that biscuits made with the addition of 25% soybean flour is the most preferred biscuit by 59% panelis with a biscuit hardness level of 29.00 mm / g / sec, carbohydrate 69.35%, fat content 15.29%, water content 6.46 %, Protein 6.42%, ash content of 2.48% and contains calories 440.69 kcalKeywords : Casein-free gluten free biscuit , Goroho plantain flour, Soybean meal